Hubungan Frekuensi Pemberian Makan Seimbang dengan Status Gizi Balita (BB/U): Hubungan Frekuensi Pemberian Makan Seimbang dengan Status Gizi Balita (BB/U) - Apriyanti, Dwi; Anis Ervina; Enzen Mafatihullah karim (Prodi DIII Kebidanan La Tansa Mashiro, 2024)
The nutritional status of toddlers is oneof the important indicators in assessingchildren's health and the future of the nation.This study aimed to analyze the relationshipbetween the frequency of balanced feedingand the nutritional status of toddlers basedon body weight for age (BB/U) and identifypotential confounding variables, such asgender, maternal age, parental education,and region of residence. This study used across-sectional design involving 143 underfives aged 48-59 months. Data were collectedthrough a structured questionnaire andstatistical analysis using the chi-square test.The results showed that 84.6% oftoddlers had ideal nutritional status, while15.4% experienced non-ideal nutritionalstatus. A total of 60.1% of toddlers were oftengiven balanced meals, and the results of theanalysis showed a significant relationshipbetween the frequency of balanced feedingwith the nutritional status of toddlers (p =0.000). Toddlers who often received balancedmeals had a higher proportion of idealnutritional status (89.5%) compared totoddlers who were rarely given balancedmeals (77.2%). There was no significantrelationship between confounding variablesand the nutritional status of children underfive (p > 0.05). The conclusion of this study confirmsthat the frequency of balanced feeding playsan important role in determining thenutritional status of children under five.Therefore, interventions that focus oneducating parents about balanced diets andincreasing access to nutritious food areneeded, especially in rural areas. Furtherresearch with a longitudinal design isrecommended to observe the long-termimpact of balanced feeding on the health ofchildren under five